The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1038/s41598-019-49266-y
|View full text |Cite
|
Sign up to set email alerts
|

Biomass-derived Carbon Quantum Dots for Visible-Light-Induced Photocatalysis and Label-Free Detection of Fe(III) and Ascorbic acid

Abstract: Visible-light-driven photocatalysts prepared using renewable resources are crucial but challenging to develop for the efficient degradation of organic pollutants, which is required to solve ever-increasing water deterioration issues. In this study, we report a visible-light-responsive photocatalyst for the efficient degradation of methylene blue (MB) as a model pollutant dye. Green-emissive carbon quantum dots (CQDs) were synthesized from pear juice via a facile, scalable, one-pot solvothermal process. The as-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(81 citation statements)
references
References 54 publications
3
73
0
Order By: Relevance
“…Many technologies have been employed to eliminate the contamination of methylene blue in the environment. Recently, physicochemical approaches, including photocatalysis, physiochemical adsorption, and non-thermal plasma technology, have garnered popularity due to its high efficiency and degradation percentage (Das et al 2019;Myung et al 2019;Wu et al 2019). However, high complexity, low economic feasibility, and disposal problems by some of these methods hinder their broad application, especially in a developing country (Zhou et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Many technologies have been employed to eliminate the contamination of methylene blue in the environment. Recently, physicochemical approaches, including photocatalysis, physiochemical adsorption, and non-thermal plasma technology, have garnered popularity due to its high efficiency and degradation percentage (Das et al 2019;Myung et al 2019;Wu et al 2019). However, high complexity, low economic feasibility, and disposal problems by some of these methods hinder their broad application, especially in a developing country (Zhou et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yu et al reported C-dots/TNS and C-dots/P25 composites with excellent photocatalytic activity for the degradation of RhB; however, there was no activity when C-dots were used alone [52]. Recently, some encouraging studies have shown that C-dots alone could possess good to excellent photocatalytic activity toward the degradation of organic dyes (Table 1, entries 5-10); however, various factors including limited light absorption, extra surface doping, as well as tedious separation have limited the practical applications of C-dots in these studies [58][59][60][61][62][63]. For instance, C-dots prepared by Srivastava and co-workers could only utilize light with a specific wavelength for the catalytic degradation of MB [59].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the rich presence of surface defects (i.e., surface functionalities) on C-dots, some of the excited carriers are trapped, and the recombination of e - and h + are hindered. As a result, the organic dyes could be oxidized by the h + directly to cause the degradation, which is well known [ 62 ]. In the meantime, some of the e − could be captured by oxygen dissolved in solution, forming super oxide radicals (i.e., •O 2 − ); some of the h + could interact with surface-adsorbed H 2 O to form hydroxyl radicals (i.e., •OH).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations